Pendekatan Diagnosa dan Tatalaksana Terkini Orbitopati Grave - Ujianto, Michelle; Sari, Felita; Rakhman, Muhammad Farid (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Graves' Orbitopathy (GO), also known as thyroid eye disease or thyroid-associated orbitopathy is characterized by inflammation, ocular muscle hypertrophy, adipogenesis, and oedema (due to glycosaminoglycan accumulation). This condition leads to remodeling, tissue expansion, and/or fibrosis within the fibroadipose tissue or extraocular muscles of the orbit. GO manifests as an extrathyroidal aspect of autoimmune thyroid diseases in both Grave's disease (GD) and Hashimoto's thyroiditis. The pathophysiological foundation of GO entails the infiltration of B cells, T cells, and CD34+ fibroblasts in the orbit. B cells generate IGF (insulin-like growth factor), wherein IGF and TRab (Thyroid-Receptor antibodies) stimulate the IGF receptor complex and thyrotropin receptor (respectively) on the surface of CD34+ cells which triggers orbital tissue expansion, orbital protrusion, optic nerve compression, and eyeball displacement, resulting in exophthalmos. GO progress through an active phase (characterized by inflammation with visible manifestations), followed by a plateau phase (stabilization of GO manifestations), and a gradual resolution of distinctive residual signs and symptoms (inactive phase). This entire process spans between 18-24 months in untreated patients, where disease manifestations significantly depend on the phase during which the disease is identified. GO therapy is intended to shorten the active phase and supress its residual eye manifestations during the inactive phase. In general, GO therapy is categorized into general and disease severity-specific approaches. GO therapy often falls short of providing satisfactory results, prompting need of surgery to address lingering clinical manifestations. This review presents the latest insights into the pathogenesis and treatment of GO for better management and outcomes.